Shoreline Dynamics and Beach Erosion - Di Paola, Gianluigi; Rodríguez, Germán; Rosskopf, Carmen M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Coasts are highly dynamic and geomorphologically complex systems that evolve under the growing pressures of climate change and anthropogenic activities, which can have direct or indirect impacts on the coastal environment. Among the major adverse effects, coastal erosion represents one of the most pressing global issues, especially in flat and low-lying coastal areas that appear to be particularly susceptible to beach erosion and related shoreline retreat. This Special Issue presents twelve papers on "Shoreline Dynamics and Beach Erosion" that contribute to the growing body of knowledge on the dynamics and spatial-temporal evolution of shorelines and beach systems. Using multi-, interdisciplinary, and new experimental approaches, coastal systems of variable complexities located in different geographic and climatic contexts are investigated. The major topics covered concern the morphodynamics and hydrodynamics of coastal systems, the driving factors of coastal erosion, and the use of models and indexes to study coastal vulnerability, and the mitigation of human and natural pressures affecting coastal ecosystems.